?SPATIAL ADAPTATION AND DEVELOPMENTAL STRATEGY IN CARBON DIOXIDE ENRICHED MUSTARD PLANTS (Biological Sciences - PJSIR, 1995)
The morphological adaptation and developmental strategy of mustard plants, grown at 330 (atmospheric), 600 and 900 ppm CO2 enriched atmosphere, are described. CO2 enrichment evoked differential response pattern to the longitudinal and spatial adaptation. An increase in the atmospheric level of CO2 resulted in increased plant height and greater number of branches .Development of assimilatory structures followed almost identical pattern corresponding to the plant height and branches. The absolute DM production was an increasing function of CO2 concentration, but with no apparent set-back on the phasic development and pattern ofDM distribution in different components indicating that increasing atmospheric CO2 concentration also improved yield capacity through increased number of pods/plant and heavier seeds but with a consistent depression in harvest index.